A ChIP-cloning approach linking SIRT 1 to transcriptional modification of DNA targets. (June 2008) - Torres, German; Frisella, Patrick D.; Yousuf, Salman J.; Sarwar, Samina; Baldinger, Lauren; Zakhary, Sherry M.; Leheste, Joerg R.
The mammalian protein deacetylase SIRT1 (sirtuin 1) is widely recognized for its link to calorie restriction and longevity. SIRT1 not only modulates the function of protein targets such as p53 or NFkappaB, but it also affects gene transcription by causing hypoacetylation of associated nucleosomal histones. However, the identification of SIRT1-specific DNA targets that confer chromosomal stability and cell longevity have remained elusive. Here, we report the usefulness of a ChIP-cloning approach for the identification of an endogenous DNA target intimately linked with SIRT1 activity. Using the aforementioned technique, we identified a gene encoding the neuro-oncological ventral antigen2 ( nova2 ) as a SIRT1 target. Nova2 regulates the alternative splicing of scn 1a, which encodes the α-subunit of a neuronal sodium channel targeted by antiepileptic drugs. This finding demonstrates that ChIP-cloning is an innovative approach for the identification of SIRT1-specific DNA targets.